PERBANYAKAN TANAMAN BUAH NAGA BERDAGING BUAH MERAH {Hylocereus costaricensis) MELALUI TEKNIK KULTUR JARINGAN - Priyono, Priyono (BERITA BIOLOGI, 2005)
Hylocereus costaricensis is new important fruit in Indonesia. One of constrain in its development is limitation of planting material.The aim of the research is to study the regeneration H. costaricensis through micro shoot induction of node explants. The experiments were carried out in the Tissue Culture Laboratory of Indonesian Coffee and Cocoa Research Institute. Experiment on microshoots proliferation stage was arranged in a Factorial Completely Randomized Design, with three replications.The first factor was Kinetin concentration consisted of five treatments i.e.: 0, 2.5, 5.0, 7.5 and 10.0 mg/1.The second factor was Indole acetic acid (IAA) concentration consisted of five levels i.e.: 0, 0.25, 0.5, 0.75 and 1 mg/1. Microshoots multiplication stage was arranged in a Factorial Completely Randomized Design,with three replications. The first factor was polyvinyl pyrrolidone (PVP) concentration consisted of six treatments i.e.: 0, 0.25, 0.5, 0.75, 1.0 and 1.25 %. The second factor was Cystein concentration consisted of four treatments i.e.: 0, 25, 50 and 75 mg/1. The microshoots rooting stage the results experiment was laid in a Factorial Completely Randomized Design, with three replications. The first factor was Giberalic acid (GA3) consisted of five treatments i.e.:0, 0.25, 0.5, 0.75 and 1 mg/1. The second factor was Boric acid concentration consisted of four levels i.e.: 0, 50, 100 and 150 mg/1. In the microshoots proliferation stage the results showed that there was interaction between IAA and Kinetin concentration on the microshoots proliferation and the number of shoot per explnat. The best results were obtained from the treatment 0.75 mg/1 IAA + 7.5 mg/1 Kinetin, whereas in this treatment the rate of microshoots proliferation and the number of microshoots perexplant was 50 % and 3.9, respectively. In the microshoots multiplication stage, the results showed that there was interaction between PVP and Cystein concentration. The best results were obtained from the treatment 0.75% PVP + 75 mg/1 Cystein, whereas in this treatment the rate of microshoots multiplication and the number of microshoots per explant was 95% and 6.3, respectively. In the rooting stage, the results showed that there was interaction between GA and Boric acid concentration. The experiment indicated that 0.5 mg/1 GA3 + 100 mg/1 Boric acid showed the best result to stimulate root induction of the in vitro microshoots propagation, whereas in this treatment the percentage of rooted microshoots and the hight of plantlet were 95% and 5.7 Cm, respectively.